Prevalence of hearing loss and tinnitus in young population in a tertiary hospital at the western region - Sharma, Swasti; Bhandari, Aakash Mani; Shakya, Ambalika; Goudel, Bonu; Gurung, Bikash (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Use of listening devices like mobile phone is very common especially in younger population. The purpose of the present study was to estimate the occurrence of hearing problems and tinnitus in young adults with exposure to leisure noise such as music via different devices.Methods: A prospective study was conducted at the Out-Patient Department of ENT, Pokhara Academy of Health Sciences, Western Regional Hospital, Pokhara, Nepal. The study was carried out for a period of one year. Patients from age 15 to 45 years presenting to the OPD with various complaints were asked about the ear problems and hearing conditions. Data acquired from the study was entered in MS Excel spreadsheet and descriptive analysis was done.Results: Total patients enrolled in the study were 105. Ear-related problems were common in studied patients. Tinnitus was observed in 37.14% and hearing problems were seen in 21.9% of cases.Conclusions: Noise exposure in the form of leisure noise can lead to ear problems like hearing loss and tinnitus.